Faith in nation - Marx, Anthony W. (Oxford University Press, 2003)
Religious intolerance--specifically the exclusion of religious minorities from the nascent state--provided the glue that bonded the remaining populations together. Out of this often violent religious intolerance grew popular nationalist sentiment. Only after a core and exclusive nationality was formed in England and France, and less successfully in Spain, did these countries move into the "enlightened" 19th century, all the while continuing to export intolerance and exclusion to overseas colonies